Legal Protection for Notaries in Implementation Tax Amnesty for Taxpayers Who Are Suspected of Committing Money Laundering Criminal Act - wardani, Rika Kurnia (Jurnal Konstatering, 2025)
Abstract. The Tax Amnesty Program in Indonesia, although aimed at improving tax compliance, has the potential for abuse and legal risks for notaries involved in making property declaration deeds. Although notaries have a crucial role in verifying taxpayers' documents and identities, the existing legal protection is not yet fully adequate, especially if the taxpayer is suspected of committing money laundering (TPPU). Therefore, this study aims to analyze legal protection for notaries in the context of Tax Amnesty and identify legal loopholes that need to be fixed. The sociological legal research method was used, including analysis of related regulations (Notary Law, TPPU Law, KUP Law, and other regulations) as well as observation of field phenomena. The results of the study indicate the need to strengthen legal protection for notaries through more comprehensive and clear regulations, as well as transparent and accountable supervision mechanisms. This study concludes that stronger legal protection is essential to prevent notaries from getting caught up in legal problems due to taxpayers' actions, while also ensuring that notaries' duties are carried out optimally. Therefore, it is recommended to revise regulations, increase supervision by professional institutions, and provide special training for notaries to understand and minimize legal risks related to TPPU.Keywords: Legal Protection; Notary; Tax Amnesty; TPPU.